Genome-wide Identification and Evolution of the PP2C Gene Family in Eight Rosaceae Species and Expression Analysis Under Stress in Pyrus bretschneideri - Wang, Guoming; Sun, Xun; Guo, Zhihua; Joldersma, Dirk; Guo, Lei; Qiao, Xin; Qi, Kaijie; Gu, Chao; Zhang, Shaoling (Frontiers in Genetics, 2021)
The type-2C protein phosphatase (PP2C) plays an essential role in abscisic acid (ABA) signaling transductions processes. In the current study, we found 719 putative PP2C genes in in eight Rosaceae species, including 118 in Chinese white pear, 110 in European pear, 73 in Japanese apricot, 128 in apple, 74 in peach, 65 in strawberry, 78 in sweet cherry and 73 in black raspberry. Further, the phylogenetic analysis categorized PbrPP2C genes of Chinese white pear into twelve subgroups based on phylogenic analysis and the orthologous pair alignment of Arabidopsis. Moreover, we observed that WGD and dispersed gene duplication (DSD) have a major contribution to PP2C family expansion. And purifying selection drove the evolution of PP2C gene family. Heatmap analysis suggested the significant role of PbrPP2C genes in various organ developments. The qRT-PCR validation of 9 PbrPP2C genes of subgroup A indicated their tolerance-related role under ABA and abiotic stress in pear. Finally, the subcellular localization analysis revealed that 5 PbrPP2C genes of subgroup A were functional in the nucleus. In summary, our outcome of the research assists to reveal the potential functions of PP2C in mediating ABA signal and various stress conditions.